Advances in In Situ Biological and Chemical Groundwater Treatment - Saponaro, Sabrina; Maletić, Snežana; Sezenna, Elena (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book collects the peer-reviewed contributions accepted for the publication in the Special Issue "Advances in In Situ Biological and Chemical Groundwater Treatment" of the MDPI journal Water. As such, the contributions refer to a variety of widespread pollutants (chlorinated ethenes, chlorinated phenols, chromium, copper, nickel, and arsenic phenols) and new remediation approaches (bioremediation, bioelectrochemical systems, and sorption), covering lab and field studies.